2021
DOI: 10.1186/s12889-021-11640-9
|View full text |Cite
|
Sign up to set email alerts
|

Electronic media use and sleep in children and adolescents in western countries: a systematic review

Abstract: Background Sleep is essential for child and adolescent health and well-being. There is an increasing interest in whether electronic media use affects children and young adolescents’ sleep. Prior reviews have focused on a school-aged population. Moreover, it is crucial that research continuously addresses the processes of technology and media use and the implication on sleep. This systematic review examines the evidence of electronic media use related to sleep among 0–15-year-olds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 75 publications
(207 reference statements)
2
51
1
Order By: Relevance
“…Adolescents’ recreational screen time was negatively associated with their sleep quality. This result confirms previous studies which reported that screen time is negatively associated with adolescents’ sleep [ 23 , 24 , 43 ]. To our knowledge, this is the first study to examine this association during the COVID-19 pandemic among adolescents in Canada.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adolescents’ recreational screen time was negatively associated with their sleep quality. This result confirms previous studies which reported that screen time is negatively associated with adolescents’ sleep [ 23 , 24 , 43 ]. To our knowledge, this is the first study to examine this association during the COVID-19 pandemic among adolescents in Canada.…”
Section: Discussionsupporting
confidence: 92%
“…In a systematic review, 90% of the studies reported that screen time negatively affected adolescents’ sleep (e.g., shorter sleep duration and later bedtime) [ 23 ]. Another systematic review reported that screen time in adolescents (13–15 years) was associated with problems falling asleep and poor sleep quality [ 24 ]. Using many screens simultaneously (i.e., concurrent screen use) has also been associated with shorter sleep duration in adolescents (11–14 years) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extended use of digital media screen time correlates with sleep impairment [ 18 , 21 , 22 , 26 , 31 , 43 , 47 , 49 , 57 , 61 , 63 , 64 , 65 ]. Table 6 summarizes the evidence in literature ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…A contributor to poor sleep is also time spent online (i.e., smartphone use, video games, social media, etc.) (Arora et al, 2014 ; Hysing et al, 2015 ; Lund et al, 2021 ). Time-consuming, it generates psycho-physiological arousal due to its content and disrupts circadian rhythms (Illingworth, 2020 ).…”
Section: Positive Psychology: Valuing Wellbeingmentioning
confidence: 99%